The Macaronesian province: patterns of species richness and endemism of arthropods - Triantis, Kostas A. (2010)
"[…]. The Macaronesian arthropod fauna displays a number of characteristics typical of oceanic islands, including a high degree of endemism, ranging from 19% for the Azores (Borges et al., 2005a), to 28% for Madeira (Borges et al., 2008a), 30% for Cape Verde (Arechavaleta etal., 2005) and 45% for the Canary Islands (Izquierdo et al., 2004; see Table I). The preponderance of endemic species has made the Macaronesian islands an outstanding area for studies of evolution and speciation, and arthropods from these islands have been the focus of particularly intensive investigation in the last ten years. Numerous biogeographic analyses of Macaronesian arthropod groups have provided valuable insights into the processes regulating species richness as well as the relationships among the region's endemics (e.g. Juan et al.,1996; Arnedo & Ribera, 1999; Borges & Brown, 1999; Emerson et al., 1999, 2006; Emerson & Oromí, 2005; Dimitrov et al., 2008; Borges & Hortal, 2009; Hochkirch & Görzig, 2009). Here we investigate the factors shaping arthropod species richness and patterns of endemism in the Macaronesian archipelagos, considering two levels of analysis: a) individual archipelagos of the Macaronesian region (except Madeira and Salvages due to their limited number of islands), and b) all the islands of the region altogether. We do this following the recently published works of Whittaker et al. (2008) and Borges & Hortal (2009), examining data sets for several taxa from the Macaronesian archipelagos. […]." (da Introdução)